The Application of Booklet as The Effort to Prepare Type 2 Diabetes Mellitus Patient in Facing New Normal Era During Covid-19 Pandemic - Fata, Ulfa Husnul; Arsa, Sandi Alfa Wega; Nurmawati, Thatit; Wibisono, Wahyu; Trijayanti, Lury; Wiratama, Danang Candra; Kuswidyarti, Yulia (Journal of Community Service for Health, 2020)
The corona virus disease pandemic has caused public health emergencies around the world. The risk, severity and mortality of this disease have been associated with chronic non-communicable diseases such as diabetes mellitus. This community service activity was carried out in September 2020. The activities were taken place in the patient's house directly (door to door). The activities were done by providing health education to people with diabetes both with and without wound complications. The respondent was 10 people. The media used booklet. Since the activity was done during the Covid-19 pandemic, both the implementing activities and the targets complied the health protocols to prevent Covid-19 transmission. The data obtained showed that the knowledge of the respondents about Covid-19 and the New Normal Era before being given health education using the booklet method was only 1 respondent had good knowledge (10%). After being given health education using the booklet method, the respondent's knowledge data about Covid-19 and the New Normal Era increased into 6 respondents (60%) had good knowledge. Booklet is one of model or media to convey health messages in the form of a book, either in writing or in pictures. Booklet has many advantages such as easy to make, can be simply made at a relatively low cost, and clients can study independently